Sliding subject positions: knowledge and teacher educators. (7th August 2015) - Brown, Tony; Rowley, Harriet; Smith, Kim
Abstract : In England, adjustments to policy in teacher education have had implications for how subject knowledge is understood and for how job descriptions are defined. That is, the interface between teacher educator and subject knowledge representation has been changing. This paper reports on a wider study that considers the experience of university teacher educators adjusting to new academic and operational conditions. On the one hand, the teacher educators are confronted with their subject specialism being set according to new learning objectives and to new time and curriculum constraints. On the other hand, their professional identity is reshaped in response to structural changes to teacher education where earlier job definitions had been reconfigured or removed. The paper analyses resultant conceptions of subject knowledge and of teacher education emerging through this changing interface and how these conceptions are variously located across staffing arrangements. A Lacanian model of subjectivity provides a theoretical approach to depicting teacher educator and pre‐service teacher identification with subject knowledge. The paper provides a theoretical account of how the teacher educator/trainee interface has been reshaped in line with the market‐led terminology that governs current practices. Specifically, the analytical tools enable us to dismantle and restructure the prevalent symbolic order guiding current teacher practice and understanding, particularly our entrapment within specific discourses and identity constructs that shape our interactions with subject knowledge.